1995
DOI: 10.1002/gcc.2870130308
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity from the short arm of chromosome 8 is an early event in breast cancers

Abstract: Loss of heterozygosity (LOH) from the short arm of chromosome 8 (8p) is common to many human carcinomas, including those of the colon and prostate. It localizes to two discrete regions, 8p21 and 8p22. This suggests the presence of at least two tumor suppressor genes (TSGs) on this chromosome arm. Human breast cancers show consistent 8p deletions in cytogenetic studies, chromosome 8 aneusomy and isochromosome 8q, indicating that the relevant gene(s) may play a role, but the results of molecular analyses of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…The ability to detect a clinical utility of 8p deletion measurement in small cohorts is obviously caused by the high rate of positive cases (almost 50%) and a particularly strong prognostic impact of this feature. It is noteworthy, however, that several other small cohorts failed to find associations with tumor phenotype 14,16,[34][35][36]59 or patient death. [34][35][36] Limitations of our study include that retrospectively collected data are used for estimating the prognostic value of 8p deletion.…”
Section: Discussionmentioning
confidence: 95%
“…The ability to detect a clinical utility of 8p deletion measurement in small cohorts is obviously caused by the high rate of positive cases (almost 50%) and a particularly strong prognostic impact of this feature. It is noteworthy, however, that several other small cohorts failed to find associations with tumor phenotype 14,16,[34][35][36]59 or patient death. [34][35][36] Limitations of our study include that retrospectively collected data are used for estimating the prognostic value of 8p deletion.…”
Section: Discussionmentioning
confidence: 95%
“…The DLC-1 gene was found to be located at 8p21.3-22 (Yuan et al, 1998), a region frequently deleted in various cancer cells including hepatocellular, lung, colorectal, prostate, and breast cancer (Emi et al, 1992;Fujiwara et al, 1994;Yaremko et al, 1995;Wistuba et al, 1999), and has been reported to be deleted in HCC cell lines and in primary tumors (Yuan et al, 1998;Ng et al, 2000). However, the mechanism of the loss of DLC-1 expression without genomic deletion has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Regions of 8p22-23 have been implicated by LOH analysis as harbouring suppressor genes relevant to the progression of many other tumour types (Suzuki et al, 1995;Yaremko et al, 1995;Bova et al, 1996). Whether these are all independent targets, or whether there are common targets inactivated in a wide variety of tumours will not be known until the relevant genes have been cloned.…”
mentioning
confidence: 99%